2014
DOI: 10.1002/bip.22410
|View full text |Cite
|
Sign up to set email alerts
|

Thermal denaturation and aggregation of apoform of glycogen phosphorylase b. Effect of crowding agents and chaperones

Abstract: The effect of protein and chemical chaperones and crowders on thermal stability and aggregation of apoform of rabbit muscle glycogen phosphorylase b (apoPhb) has been studied at 37°C. Proline suppressed heat-induced loss in ability of apoPhb to reconstitution at 37°C, whereas α-crystallin did not reveal a protective action. To compare the antiaggregation activity of intact and crosslinked α-crystallins, an adsorption capacity (AC) of a protein chaperone with respect to a target protein was estimated. This para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The reason of the appearance of the sensitivity of the nucleation stage and the stages of clusterization of nuclei to crowding is incorporation of ␣-crystallin particles in nuclei and their clusters. ␣-Crystallin particles possess dynamic structure and show a capacity for intermolecular exchange of subunits and partial dissociation into suboligomeric forms when interacting with target protein [9,15,[48][49][50][51][52][53][54][55][56]. Carver and coworkers showed that the rate of subunit exchange of ␣A-crystallin decreased under crowding conditions [57].…”
Section: Methodsmentioning
confidence: 99%
“…The reason of the appearance of the sensitivity of the nucleation stage and the stages of clusterization of nuclei to crowding is incorporation of ␣-crystallin particles in nuclei and their clusters. ␣-Crystallin particles possess dynamic structure and show a capacity for intermolecular exchange of subunits and partial dissociation into suboligomeric forms when interacting with target protein [9,15,[48][49][50][51][52][53][54][55][56]. Carver and coworkers showed that the rate of subunit exchange of ␣A-crystallin decreased under crowding conditions [57].…”
Section: Methodsmentioning
confidence: 99%
“…The anti-aggregation activity of protein chaperones can be characterized by the value of the initial stoichiometry of the chaperone-target protein complex (S 0 ) and can be determined from the initial linear part of the dependence of v 0 on the [chaperone]/[UV-Phb] ratio [41]:…”
Section: The Effect Of Arg On the Chaperone-like Activity Of Hspb6 Anmentioning
confidence: 99%
“…(apoPhb) of rabbit origin [12], while Aquaporin 0 (AQP0) aggregates at 60 • C [13], bovine hemoglobin aggregates at ∼70 • C [14], recombinant human interferon alpha2b (rhIFN␣2b) aggregates at 50 • C [15] while SARS-associated corona virus (SARS-CoV) protein aggregates at most extreme condition i.e. boiling temperature [16].…”
Section: Introductionmentioning
confidence: 99%